Pengaruh Pengetahuan dan Sikap Terhadap Kepatuhan Ibu Hamil Dalam Pemeriksaan ANC Pada Masa Pandemi di Poskesdes Bungadidi Kec. Tana Lili - Nisma; Sundari; Fatmah Afrianty Gobel (Program Pascasarjana Universitas Muslim Indonesia, 2021)
Background: The Covid-19 pandemic is profoundly changing the status of everyday life around the world as people are forced to social distancing and self-isolation, and to work from home via the internet. All these sudden changes impose a huge psychological burden on all individuals and especially for pregnant women who are now facing their pregnancies with more anxiety and uncertainty than ever before. The purpose of this study was to analyze the compliance of pregnant women to the ANC examination during the pandemic at the Bungadidi Poskesdes, Tana Lili District. Method: This type of research is analytic with a quantitative approach. The research design used cross sectional. From the results of statistical calculations, the number of samples needed in this study was 96 samples. Results: There was an influence of predisposing factors of knowledge and attitudes on ANC examinations at Poskesdes Bungadidi, Tana Lili District. Conclusion: It is hoped that this research can provide information about the current situation of Covid-19 and increase public knowledge and awareness about the prevention and transmission of Covid-19 in the surrounding environment, especially for pregnant women.